O professor Afonso Pereira da Silva e a expansão da educação na Paraíba (1954-1974) - Sabino, Raquel do Nascimento (2021)
This study aims to understand the role of Professor Afonso Pereira da Silva in Paraíba’s education from 1954 to 1974, a period that includes the year of the creation of the Padre Ibiapina Foundation by the educator and the year he left the direction of that institution. Inscribed in the field of the theoretical-methodological approach of New Cultural History, it seeks to study the educator from the roles he played, his performance as a teacher and his connection with the cultural sphere, his social practices, the means, and places for the dissemination of knowledge by which he circled. From a methodological point of view, this is a bibliographical and documentary research in the collection of authors who focus on the New Cultural History: Chartier (1994;2002), Le Goff (2011;2013), Pesavento (2003), and Burke (1992; 2005); and on the study of Sirinelli intellectuals (1994; 1998; 2003). We support the conception of the new cultural history aimed at the dissemination and reception of cultural products, dialoguing with the categories: itineraries, sociability networks and circulation of ideas. We brought a debate about the scholar as an object/subject of research in History of Education, placing Professor Afonso Pereira da Silva as a creative and mediating intellectual due to the nature of his performance in spaces of circularity. We present a biographical clipping of the life of Professor Afonso Pereira da Silva, his professional trajectory, and his engagement in the expansion of education in Paraíba through the creation of the Padre Ibiapina Foundation and launch of schools. The main sources used in this study were the reports made by Afonso Pereira about the activities of the Padre Ibiapina Foundation, his personal documents, his written productions, the Foundation's minutes, and its correspondence, located in the archives of the Afonso Pereira Archive in the city of João Pessoa; other sources added to the study such as newspapers that circulated in Paraíba and neighboring states, educational legislation and pictorial representations, photographs. The study revealed that through his practices, Afonso Pereira contributed to the cultural and educational scenario of Paraíba, acting especially as an agent in the expansion of education in Paraíba through the stablishing of schools in a context of marked lack of education provision in the interior of the state.